guide to successful bioprospecting: informed by actinobacterial systematics - Goodfellow, Michael; Fiedler, Hans-Peter (Antonie van Leeuwenhoek, 2010)
New structurally diverse natural products are discovered when novel screening procedures are introduced or when high quality biological materials from new sources are examined in existing screens, hence it is important to foster these two aspects of novelty in drug discovery programmes. Amongst prokaryotes, actinomycetes, notably streptomycetes, remain a rich source of new natural products though it has become increasingly difficult to find such metabolites from common actinomycetes as screening ‘old friends' leads to the costly rediscovery of known compounds. The bioprospecting strategy which is the subject of this review is based upon the premise that new secondary metabolites can be found by screening relatively small numbers of dereplicated, novel actinomycetes isolated from marine sediments. The success of the strategy is exemplified by the discovery of a range of novel bioactive compounds, notably atrop-abyssomicin C and proximicins A, B and C from Verrucosispora strains isolated from sediment samples taken from the Sea of Japan and the Raune Fjord, respectively, and the dermacozines derived from Dermacoccus strains isolated from the Challenger Deep of the Mariana Trench in the Pacific Ocean. The importance of current advances in prokaryotic systematics in work of this nature is stressed and a plea made that resources be sought to train, support and employ the next generation of actinobacterial systematists.